PENERAPAN PIDANA DENDA PENGGANTI DALAM TINDAK PIDANA NARKOTIKA (ANALISIS PUTUSAN NOMOR : 2050/PID. SUS/2021/PN TNG) - Elang Pramudya, Mohamad; Widarto, Bambang (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
In 2021, the Tangerang District Court in verdict number 2050/Pid. Sus/2021/PN Tng, sentenced the defendant to 9 (nine) years of imprisonment for drug abuse and a fine of IDR 3,000,000.00, provided that if the fine is not paid, it will be replaced by imprisonment for 3 (three) months. The formulation of the problem, How is the application of substitute fines in Decision Number: 2050/Pid. Sus/2021/PN Tng ? and How is the application of substitute fines in Decision Number: 2050/Pid. Sus/2021/PN Tng ?. This research method uses normative legal research methods with a statutory approach and conceptual approach and uses secondary, primary and tertiary data. The results of the research obtained that the substitute fine imposed by the judge is lower than the maximum fine as stipulated in article 114 paragraph (2) Jo article 132 paragraph (1), namely the maximum fine as referred to in paragraph (1) plus 1/3 (one third), if you look at article 114 paragraph (1) the maximum fine is 10 (ten) billion if added by one third to around 13 (thirteen) billion while the judge's decision is 3 (three) billion. In this case, the judge considers the decision not only for economic purposes or just to increase state financial income, but is related to the achievement of the objectives of punishment, which considers the values of legal certainty, justice and expediency, the application of substitute fines in Decision Number: 2050/Pid.Sus/2021/Pn.Tng is in accordance with the provisions of Law Number 35 of 2009 concerning Narcotics Crimes. It is suggested that the substitute fine be given to the defendant as much as possible to provide a deterrent effect.